Memberdayakan Anak Jalanan Melalui Pendidikan: Pendirian Kampung Anak Negeri di Kelurahan Wonorejo Kec. Rungkut Surabaya - Kinanti Resmi Hayati; Lely Febriana; Novita Candra Puspita; Vika Agustin (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research program is carried out at UPTD Kampung Anak Negeri, Surabaya City, this UPTD serves someone who has social welfare problems. UPTD Kampung Anak Negeri has the function of fostering street children. This UPTD fosters street children directly, this is proven by the availability of many social empowerment facilities at UPTD Kampung Anak Negeri, as well as learning activity programs that have been determined and carried out in an orderly manner. The research we use here is qualitative research with descriptive methods. The population in this study is the children of UPTD Kampung Anak Negeri Surabaya City. The number of members of the population is 38 foster children who are male - male. The population has a vulnerable age of 9-19 years. UPTD Kampung Anak Negeri Kota Surabaya is an empowerment of street children who build a number of street and abandoned children in Surabaya. The activities provided are useful for children to meet their future.